(Re-)discovering comparative theology: An Australian perspective. (February 2014) - Ray, Anita C.
A revitalized discipline of comparative theology emerged within the Anglo-American academy towards the close of the 20th century and within German universities at the beginning of the present century. It has recently begun to show promising signs of life in Australia. This article seeks to evaluate the endeavour, identifying the essential traits of the comparativist, the distinctive features of the enterprise and the major scholarly critiques surrounding the venture. I argue that the rejuvenated discipline embodies a compelling intellectual and spiritual exercise and a constructive way forward for theological enquiry in a world where multiple religious groups stand in close proximity to one another. Finally, I interrogate the feasibility of doing comparative theology with Indigenous Australian and Torres Strait Islander peoples, who preserve their spiritual wisdom in oral traditions rather than written texts.